ACUTE DETRIMENTAL EFFECTS OF E-CIGARETTE AND TOBACCO CIGARETTE SMOKING ON BLOOD PRESSURE AND SYMPATHETIC NERVE ACTIVITY IN HEALTHY SUBJECTS. (June 2018) - Dimitriadis, K.; Tsioufis, K.; Konstantinidis, D.; Kalos, T.; Fragoulis, C.; Konstantinou, K.; Mantzouranis, M.; Vogiatzakis, N.; Tousoulis, D.
Abstract : Objective: This study aimed to assess the acute effects of tobacco cigarettes, e-cigarettes and sham smoking on blood pressure and sympathetic nervous system in healthy subjects. Design and method: We studied 10 normotensive male habitual smokers (mean age 33 years, body mass index: 24.1 kg/m2, office blood pressure = 117/72 mmHg) free of cardiovascular disease. The study design was randomized and placebo controlled with 3 experimental sessions. Subjects smoked 2 tobacco cigarettes containing 1.1 mg nicotine or simulate smoking (sham smoking) with the 2 cigarettes separated by 5 minutes, while 45 minutes after finishing the second cigarette, subjects smoked a third cigarette or sham cigarette. Additionally, participants smoked e-cigarettes for a period of 5 and 30 minutes. Sympathetic drive was assessed by muscle sympathetic nerve activity (MSNA) (baroreflex-dependent) and skin sympathetic nerve activity (SSNA) (baroreflex-independent). Results: After the first, second and third tobacco cigarette smoking there was an increase in mean arterial pressure (by 11.2 ± 1.4%, 12.3 ± 1.3% and 13.1 ± 1.4%, respectively, p < 0.05 for all) and heart rate (by 25.1 ± 3.7%, 26.3 ± 2.7% and 25.9 ± 3.7%, respectively, p < 0.05 for all). Similarly e-cigarette smoking at 5 and 30 minutes was accompanied by augmentation of mean arterial pressure (by 10.9 ± 1.2% and 12.8 ± 1.4%, respectively, p < 0.05 for both) and heart rate (by 22.5 ± 3.3% and 23.9 ± 3.8%, respectively, p < 0.05 for both). The first, second and third tobacco cigarette smoking was accompanied by lower MSNA (by 28.1 ± 4.4%, 29.6 ± 5.3% and 30.1 ± 5.2%, respectively, p < 0.05 for all), whereas SSNA was increased (by 98.2 ± 19.4%, 100.2 ± 22.7% and 101.5 ± 21.6%, respectively, p < 0.05 for all). Additionally, e-cigarette smoking at 5 and 30 minutes caused a decrease in MSNA (by 26.9 ± 3.6%, and 28.3 ± 5.1%, respectively, p < 0.05 for both), and an augmentation in SSNA (by 97.9 ± 20.1% and 100.9 ± 20.6%, respectively, p < 0.05 for both). Sham smoking was devoid of any effects on blood pressure, MSNA and SSNA. Conclusions: E-cigarette smoking acutely increases blood pressure and has a detrimental effect on sympathetic nerve activity regulation similar to tobacco smoking in healthy subjects.